Listening to locals: regional spaces in higher education in the global south - Chankseliani, M; Sopromadze, N (Elsevier, 2023)
One of the contemporary trends in global higher education is the emergence of regional spaces that transcend national boundaries, fostering cross-border integration and cooperation. This paper presents original data from surveys of university international officers and interviews with national policy-makers to explore regional spaces in higher education across the Caucasus (Armenia, Azerbaijan, Georgia) and Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan). The findings unveil a complex landscape of spatial identities marked by diversity and tensions. The European space is recognised as by far the most important space in higher education. At the same time, the Eurasian/the Commonwealth of Independent States’ space(s) remain to be prominent in higher education, albeit to a varying degree in different countries. The study also observes the nascent development of immediate geographic spaces in Central Asia and the Caucasus, where participants express enthusiasm for collaborative efforts with neighbouring countries to advance common interests in higher education and research.